Implementasi Algoritma Best-First Search (BeFS) pada Penyelesaian Traveling Salesman Problem (TSP) (Studi Kasus: Perjalanan Wisata Di Kota Yogyakarta) - Muchammad Abrori; Rike Nur Setiyani (Jurnal Fourier, 2015)
Yogyakarta offers many tourist attractions, from nature based tourism, culinary tourism until cultural tourism. With so many tourist attractions offered by Yogyakarta, tourist often finds it difficult to arrange their travel schedule (from choosing which tourist attractions to be visited until choosing which route tourist should takes to maximize their vacation time). Therefore, it’s required to have a way to determine the shortest tour route so tourist can make their tour in the Yogyakarta effective. This problem can be categorized as Traveling Salesman Problem (TSP) case. There are a lot of methods can be used to find the shortest route in Travelling Salesman Problems (TSP) case. To solve the problem, which is to find the shortest tour route in Yogyakarta, Algorithm Best-First Travelling will be used in this undergraduate thesis. The implementation of Algorithm Best-First Search to find the shortest tour route in Yogyakarta can be used to produce a solution for tourist to choose the shortest tour package and decide which route they should take. The premium tour package produces tour route from Adi Sucipto Airport-Gembira Loka Zoo- Purawisata-N’dalem Gamelan Hotel-Yogyakarta Palace-Benteng Vredeburg Museum-Taman Pintar-Tamansari-Adi Sucipto Airport with distance covered 20.297 meter. The middle tour package produces tour route from Tugu railway station-Benteng Vredeburg Museum- Taman Pintar-Yogyakarta Palace-Mawar Asri Hotel-Tamansari-Purawisata-Gembira Loka Zoo-Tugu railway station with distance covered 11.772 meter. The economy tour package produces tour route from Giwangan bus station- Gembira Loka zoo-Purawisata-Yogyakarta Palace-Mitra Hotel-Benteng Vredeburg Museum-Taman Pintar-Tamansari-Giwangan bus station with distance covered 14.037 meter.